The Influence of Pain Severity and Interference on Satisfaction with Pain Management among Middle-Aged and Older Adults. (22nd December 2016) - Baker, Tamara A.; Krok-Schoen, Jessica L.; O'Connor, Melissa L.; Brooks, Amber K.
Abstract : Background . Health outcomes are often contingent on how effective the individual is able to manage existent illness-related symptoms. This is all the more relevant among chronic pain patients. Objective . This study aimed to identify indicators of pain treatment satisfaction among middle-aged and older adults (N = 150 ) receiving outpatient treatment from a comprehensive cancer center. Methods . Patients were surveyed on questions assessing pain treatment satisfaction, pain severity, and additional social characteristics. Results . Descriptive data showed that middle-aged adults reported more pain locations, greater pain severity, and less satisfaction with pain treatment. A multivariate model was specified, showing older adults being more satisfied with their pain treatment. For the middle-aged adults, treatment satisfaction was generally lower with greater pain severity. This counters that for the older adults, where treatment satisfaction remained consistent despite increased levels of pain severity. Conclusion . These findings address an important issue regarding how pain is experienced across the life course. This suggests that general assumptions cannot be made about the health outcomes of older adults. Beyond the descriptive definitions of pain, there remains the need to develop models that account for determinants that may account for the pain experience among a diverse adult population.